Health for sale: the medicinal plant markets in Trujillo and Chiclayo, Northern Peru - Vandebroek Ina; Sharon Douglas; Bussmann Rainer W; Jones Ana; Revene Zachary (BMC, 2007)
Abstract Traditional methods of healing have been beneficial in many countries with or without access to conventional allopathic medicine. In the United States, these traditional practices are increasingly being sought after for illnesses that cannot be easily treated by allopathic medicine. More and more people are becoming interested in the knowledge maintained by traditional healers and in the diversity of medicinal plants that flourish in areas like Northern Peru. While scientific studies of medicinal plants are underway, concern has arisen over the preservation of both the large diversity of medicinal plants and the traditional knowledge of healing methods that accompanies them. To promote further conservation work, this study attempted to document the sources of the most popular and rarest medicinal plants sold in the markets of Trujillo (Mayorista and Hermelinda) and Chiclayo (Modelo and Moshoqueque), as well as to create an inventory of the plants sold in these markets, which will serve as a basis for comparison with future inventories. Individual markets and market stalls were subjected to cluster analysis based on the diversity of the medicinal plants they carry. The results show that markets were grouped based on the presence of: (1) common exotic medicinal plants; (2) plants used by laypeople for self-medication related to common ailments ("everyday remedies"); (3) specialized medicinal plants used by curanderos or traditional healers; and (4) highly "specialized" plants used for magical purposes. The plant trade in the study areas seems to correspond well with the specific health care demands from clientele in those areas. The specific market patterns of plant diversity observed in the present study represent a foundation for comparative market research in Peru and elsewhere.